Oxyresveratrol as a novel ferroptosis inducer exhibits anticancer activity against breast cancer via the EGFR/PI3K/AKT/GPX4 signalling axis - Xiang, Lei; Li, Qingzhou; Guan, Zhiwei; Wang, Guilin; Yu, Xiankuo; Zhang, Xianwen; Zhang, Guochen; Hu, Jushan; Yang, Xue; Li, Mingrui; Bao, Xilinqiqige; Wang, Yumei; et al. (Frontiers in Pharmacology, 2025)
IntroductionOxyresveratrol (ORes) exhibits significant anticancer activity, particularly against breast cancer. However, its exact mechanism of action (MOA) remains unclear. This study aimed to investigate the pharmacological activity and underlying MOA.MethodsThe inhibitory effect of ORes on breast cancer cell growth was confirmed, and the effective concentrations were determined for further experiments. Gene expression profiles (GEPs) were collected from MDA-MB-231 cells treated with ORes at varying concentrations using HTS2. Bioinformatics tools were used to predict the anticancer activity and MOA of ORes. Ferroptosis markers (ferrous ions, reactive oxygen species, lipid peroxidation, and GPX4 expression) were assessed, and mitochondrial morphology was observed. The effect of ORes on tumour growth was evaluated in vivo, along with the analysis of ferroptosis in tissues. The MOA was explored using L1000, Drug Gene DataBase (DGDB), and Western blotting analyses.ResultsORes significantly reduces breast cancer cell viability and proliferation in a concentration-dependent manner, with IC50 values of 104.8 μM, 150.2 μM, and 143.6 μM in MDA-MB-231, BT-549, and 4T1 cells, respectively. GEPs induced by ORes were significantly enriched in the ferroptosis and PI3K/AKT signalling pathways. ORes inhibited breast cancer cell growth, increased intracellular ferrous ion levels, reactive oxygen species, and lipid peroxidation, and induced ferroptosis-related mitochondrial alterations. These effects were associated with decreased GPX4 expression and suppression of EGFR, phosphorylated PI3K, and phosphorylated AKT. ORes inhibited tumour growth, enhanced iron deposition, and reduced GPX4 expression in tumour tissues in vivo. Notably, treatment with the ferroptosis inhibitor ferrostatin-1 (Ferr-1) attenuated the anticancer effects of ORes, confirming the pivotal role of ferroptosis in ORes-mediated breast cancer inhibition.ConclusionORes inhibits breast cancer cell growth by inducing ferroptosis through suppression of the EGFR/PI3K/AKT/GPX4 signalling axis. This study suggests that ORes holds promise as a potential therapeutic agent for breast cancer and warrants further investigation into its clinical applications and potential integration into existing treatment regimens.